Turkish Validity and Reliability Study of (Trait) Empathic Anger Scale - Nur Okutan (Muhammed Yıldız, 2019)
The present study aims to adapt (Trait) Empathic Anger Scale (Vitaglione & Barlett, 2003) into Turkish and examine its psychometric properties. Empathic anger is defined as a feeling that is felt for the victim in the event of an injustice. This emotion also creates a desire to help the victim and punish the violator. The sample consisted of 225 undergraduate students (175 women, 49 men, undetermined 1). Data was collected by (Trait) Empathic Anger Scale, Interpersonal Reactivity Index, Moral Identity Scale, and demographic information form. Factor structure of the scale was tested with exploratory and confirmatory factor analyses. The results of the exploratory factor analysis indicated that a single factor measurement model. The variance explained by the model is 42.15%. The maximum likelihood estimation technique was used in confirmatory factor analysis. The results showed that the validity of the single factor measurement model was confirmed by confirmatory factor analysis. The Empathic Anger Scale had a positive relationship with the cognitive (perspective taking and fantasy) and emotional dimensions (empathic concern and personal distress) of empathy. A similar positive relationship was also observed between the empathic anger and the internalization sub-factor of moral identity. These results have proved the criterion validity of the scale. Also, the significance of the difference between the two groups with the highest and lowest scores indicated that the (Trait) Empathic Anger Scale is a valid scale. The reliability of the scale was supported by Cronbach Alpha’s internal consistency coefficient (0.71) and two-half and test-retest reliability values. Consequently, the validity and reliability of the analysis results indicated that the (Trait) Empathic Anger Scale is a valid and reliable measurement tool.